Enhanced chloroplast FtsZ-ring constriction by the ARC6–ARC3 module in Arabidopsis - Wenbin Du; Lingyan Cao; Yuelong Zhou; Shanelle Jackson; Maryam Naeem; Zhaoyu Chen; Yue Yang; Jonathan M. Glynn; Katie J. Porter; Runlong Zhang; Qian He; Moyang Liu; et al. (Proceedings of the National Academy of Sciences, 2025)
Chloroplast division, a process tightly linked to the energy demands of plants, is initiated by the formation of the stromal filamenting temperature-sensitive Z (FtsZ) ring. The Z ring is highly dynamic, and its constriction provides the essential force for chloroplast division. However, the regulatory mechanisms governing Z-ring dynamics and constriction remain poorly understood. Here, we report that the chloroplast inner envelope membrane (IEM) protein ACCUMULATION AND REPLICATION OF CHLOROPLASTS6 (ARC6) interacts with the chloroplast stromal protein ARC3, and this interaction is negatively regulated by the conserved J-like domain of ARC6. ARC3 is found both distributed throughout the stroma and localized to a ring-like structure at the chloroplast division site. We demonstrate that ARC6 recruits ARC3 to the division site to form a ring-like structure, likely through direct interaction. This ARC6–ARC3 interaction enables ARC3 to bind FtsZs. Furthermore, we show that the ARC6–ARC3 complex significantly promotes the dynamics of chloroplast Z rings reconstituted in a heterologous system. Finally, the constriction of these reconstituted Z rings is markedly enhanced by ARC6–ARC3. Our findings reveal a regulatory mechanism that governs Z-ring dynamics and constriction, shedding light on the molecular mechanisms underlying chloroplast division.